Carbon saturation of silicon target under the action of pulsed high-intensity ion beam; IOP Conference Series: Materials Science and Engineering; Vol. 110 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2015) - Aktaev N. E. Nurken Erbolatovich (2016, 2016)
Title screen